An educational multimedia system to geoscience education: a modern strategy for the diffusion of paleontological knowledge in basic education - Reis, Márcia Aparecida Fernandes dos; Carvalho, Carlos Vitor de Alencar; Carvalho, Janaína Veiga; Rodrigues, Maria Antonieta da Conceição; Medeiros, Marco André Malmann; Villena, Hélio Heringer; Oliveira, Fernanda Marini de; Dornelas, Viviane Rezende (Anuário do Instituto de Geociências, 2005)
The knowledge and diffusion of palaeontology concepts is of extreme importance for a more complete understanding of biological, geological and environmental aspects. However, it is well-known that didactic resources are still necessary to their diffusion and to stimulate the interest of first degree students. In order to develop strategies allowing the transference of palaeontological knowledge in a more dynamic and attractive manner, an educational CD-ROM about the São José de Itaboraí Basin, in the Rio de Janeiro State, South-Eastern Brazil has been elaborated and is presented here. It is the first major project aimed at the diffusion of palaeontology, through the presentation of the main fossil-related Basins of Brazil, using computing resources applied to education. This multimedia system contains geological and palaeontological information about the São José de Itaboraí Basin, using texts, fossil pictures and their present representatives, maps, outline drawings, references, glossary, palaeoenvironmental reconstitutions and fixation exercises. This didactic resource shall provide college (future teachers) and first degree students and teachers with a dynamic resource to complete and improve their knowledge about geology and palaeontology. This CD-ROM is an important virtual tool for the diffusion of the scientific and cultural importance of the São José de Itaboraí Basin to pupils at local schools, stimulating the preservation of this important natural monument of the Rio de Janeiro State.